Emergência de ditado ao longo do ensino cumulativo de discriminações condicionais entre palavras ditadas e impressas - Garcia, Christian David Pineda (Universidade Federal de São Carlos, 2017)
The current work involves assessing a computerized teaching module grounded within the stimulus equivalence paradigm. This method has been successfully used for teaching reading and spelling skills to children with a poor educational history. The primary tasks employed by the matching-to-sample procedure constitute of matching pictures with dictated words, printed words with dictated words and printed syllables with dictated syllables. The goal is to teach relations between stimuli through the establishment of listening repertoires. Another task is to copy, which involves selection of printed letters conditionally upon the presentation of printed words. Across the 17 teaching steps of Module 1, these four tasks are performed with three different words. Periodic probes measure the emergence of untrained skills, such as reading (textual behavior), writing under dictation control, and conditional relations between the printed words and pictures, and vice versa. Previous studies have shown that upon conclusion of the module, students demonstrate high indicators of success in all emerging skills. The goal of the current study was to examine in detail dictation emerged performances through the 17 teaching steps, describing the acquisition pattern for each participant when writing dictated words. The data of 12 students who completed Module 1 served as a baseline at the beginning of the study. Each step involved the presentation of a word and two attempts of intercalated dictations along with other tasks. Six trials were made for each step, with 102 trials for the whole module. The number of trials and corresponding steps was repeated until an accuracy criterion of 100% was met for each step. Cumulative response curves were categorized into three general patterns of spelling: immediate, progressive (intermediate or late) and oscillatory emergency. For the immediate emergence, the participant produced correct responses across most trials. In the progressive emergence, the student produced several incorrect responses at onset, but shifted to a progressively more accurate pattern with subsequent steps. In the oscillatory pattern, the participant initially produced correct responses but, in subsequent steps, the production of incorrect responses increased. Analysis of writing topographies and average correct percentages on bigrams demonstrated improved performances across writing repertoires compared to the first steps, indicating the emergence of dictation repertoires. Analysis of teaching steps repetitions suggested distributions similar to those presented across the cumulative response curves (i.e., immediate, progressive and oscillatory patterns). Pearson correlations were found across baseline reading and spelling scores, with a strong relationship between the acquisition of reading and spelling repertoires. An inverse relation between initial performances and amount of training and age. Other correlations were observed across scores reached in the initial tasks used to measure the relation between spoken words and printed words (AC relation) and participant’s age to the amount of training needed for participants. In conclusion, it is fair to say that the dictation by composition emerged for all participants, although in different levels. Future research could tackle the variables responsible for the variability of participant’s performances.
Keywords: Escrita; Leitura; Equivalência de estímulos; Relações emergentes; Aquisição de ditado; Ensino fundamental; Spelling; Reading; Stimulus equivalence; Emergent relations; Dictation performance acquisition; Elementary school; CIENCIAS HUMANAS::PSICOLOGIA